Hypertensive response to exercise in adult patients with repaired aortic coarctation. Issue 14 (5th January 2022) - Meijs, Timion A; Muller, Steven A; Minderhoud, Savine C S; de Winter, Robbert J; Mulder, Barbara J M; van Melle, Joost P; Hoendermis, Elke S; van Dijk, Arie P J; Zuithoff, Nicolaas P A; Krings, Gregor J; Doevendans, Pieter A; Spiering, Wilko; et al.
Abstract : Objective: The clinical and prognostic implications of a hypertensive response to exercise after repair of coarctation of the aorta (CoA) remain controversial. We aimed to determine the prevalence of a hypertensive response to exercise, identify factors associated with peak exercise systolic blood pressure (SBP) and explore the association of peak exercise SBP with resting blood pressure and cardiovascular events during follow-up. Methods: From the Dutch national CONgenital CORvitia (CONCOR) registry, adults with repaired CoA who underwent exercise stress testing were included. A hypertensive response to exercise was defined as a peak exercise SBP ≥210 mm Hg in men and ≥190 mm Hg in women. Cardiovascular events consisted of coronary artery disease, stroke, aortic complications and cardiovascular death. Results: Of the original cohort of 920 adults with repaired CoA, 675 patients (median age 24 years (range 16–72 years)) underwent exercise stress testing. Of these, 299 patients (44%) had a hypertensive response to exercise. Mean follow-up duration was 10.1 years. Male sex, absence of a bicuspid aortic valve and elevated resting SBP were independently associated with increased peak exercise SBP. Peak exercise SBP was positively predictive of office SBP (β=0.11, p<0.001) and 24-hour SBP (β=0.05, p=0.03) at follow-up, despite correction for baseline SBP. During follow-up, 100 patients (15%) developed at least 1 cardiovascular event. Peak exercise SBP was not significantly associated with the occurrence of cardiovascular events (HR 0.994 (95% CI 0.987 to 1.001), p=0.11). Conclusions: A hypertensive response to exercise was present in nearly half of the patients in this large, prospective cohort of adults with repaired CoA. Risk factors for increased peak exercise SBP were male sex, absence of a bicuspid aortic valve and elevated resting SBP. Increased peak exercise SBP independently predicted hypertension at follow-up. These results support close follow-up of patients with a hypertensive response to exercise to ensure timely diagnosis and treatment of future hypertension.